2020
DOI: 10.1155/2020/8016531
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of Oral Chinese Patent Medicines Combined with Chemotherapy for Gastric Cancer: A Bayesian Network Meta‐Analysis

Abstract: Objectives. This network meta-analysis (NMA) was designed to assess the comparative effectiveness and safety of oral Chinese patent medicines combined with chemotherapy for gastric cancer on the National Basic Medical Insurance Drugs List of China. Methods. A comprehensive literature search was performed in seven electronic databases from their inception to February 25, 2020, aiming to collect all related randomized controlled trials (RCTs) to evaluate the effectiveness and safety of oral Chinese patent medici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…After removing 26 duplicates, 92 titles and abstracts were further screened. Finally, 20 systematic reviews with MAs ( Xie et al, 2013 ; Yang et al, 2013 ; Li et al, 2014 ; Wang et al, 2014 ; Yao et al, 2014 ; Li et al, 2015 ; Wang et al, 2015 ; Zhang et al, 2017 ; Zhang D. et al, 2018 ; Zhang X. et al, 2018 ; Chen et al, 2018 ; Lee et al, 2018 ; Wu et al, 2018 ; Sun et al, 2019 ; Wu et al, 2019 ; Lu X. et al, 2020 ; Chen et al, 2020 ; Li et al, 2020 ; Wu et al, 2020 ; Cheng et al, 2021 ) in English that focused on CM for gastric cancer were included (no different MA was identified from the reference lists). The selection flow used in this research is displayed in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After removing 26 duplicates, 92 titles and abstracts were further screened. Finally, 20 systematic reviews with MAs ( Xie et al, 2013 ; Yang et al, 2013 ; Li et al, 2014 ; Wang et al, 2014 ; Yao et al, 2014 ; Li et al, 2015 ; Wang et al, 2015 ; Zhang et al, 2017 ; Zhang D. et al, 2018 ; Zhang X. et al, 2018 ; Chen et al, 2018 ; Lee et al, 2018 ; Wu et al, 2018 ; Sun et al, 2019 ; Wu et al, 2019 ; Lu X. et al, 2020 ; Chen et al, 2020 ; Li et al, 2020 ; Wu et al, 2020 ; Cheng et al, 2021 ) in English that focused on CM for gastric cancer were included (no different MA was identified from the reference lists). The selection flow used in this research is displayed in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…According to Zhang et al ( Zhang et al, 2017 ), a comparison between ten CM injections combined with FOLFOX and FOLFOX alone revealed that the combinations of astragalus, FFKS, KangAi, lentinan, HuaChanSu, and SQFZ with FOLFOX improved the objective response rate. Lu et al ( Lu X. et al, 2020 ) demonstrated that when seven oral Chinese patent medicines (e.g., BaZhen granule, Cinobufacin capsule, and XiaoAiPing tablet) combined with chemotherapy were compared to chemotherapy alone, the BaZhen granule combined with chemotherapy ranked first in terms of objective response rate. However, a network MA conducted by Zhang et al ( Zhang D. et al, 2018 ) showed no obvious difference between 11 CM injections (e.g., AiDi, KangAi, HuaChanSu, and FFKS) combined with XELOX compared to XELOX alone in terms of objective response rate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, previous studies have shown that a TCM named Yiqi Jianpi Hewei could alleviate the occurrence rate of chemotherapy induced constipation in breast cancer patients (Wu et al, 2019;Li et al, 2020). The SST has been used to restore the immune function of chemotherapeutic or post-operational period gastric cancer patients (Lu et al, 2020). However, the mechanisms of pharmacodynamics and drug-drug interaction remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with Chinese herbal medicine and Chinese herbal injection, OCPM has the advantages of convenient management and accurate dosage, which have been generally accepted and widely used in Chinese clinical practice. 6 Some studies have provided evidence that the combination of OCPM and chemotherapy can obtain a better clinical efficacy in the treatment of CRC. 7 , 8 However, there is a lack of head-to-head comparisons between different OCPM, and its relative advantages have not been well understood.…”
Section: Introductionmentioning
confidence: 99%